The Measurement and Control of Credit Risk in the Chinese Banking Sector and the Application of CreditMetrics Model - Guo, Xiaofei (2006)
Financial globalization, increased volatility of financial markets and rapid developments in financial engineering has dramatically increased the risks of a bank's trading position. Of the major risks involved in banking management, credit risk is regarded as the major risk in terms of its influence on bank performance and bank failure.